2022
DOI: 10.1155/2022/3129638
|View full text |Cite|
|
Sign up to set email alerts
|

An Annealing Model Analysis and Research on the In of Community Public Sports on Economic Development

Abstract: The state vigorously develops the application of community sports and takes it as an important unit of social and economic development. With the development of the economy, residents’ living standards are getting better, which also greatly promotes the development of community public sports. Community public sports have made great progress in terms of scale, hardware, and services, and their impact on society is getting worse. Come bigger. However, there are still some deficiencies in the development of commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The results are shown in Figure 6 . In addition, in terms of experimental environment and experimental effect, the results of basketball program are ideal, which is basically in the position of median line, indicating that the comprehensiveness of the two indexes is strong [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are shown in Figure 6 . In addition, in terms of experimental environment and experimental effect, the results of basketball program are ideal, which is basically in the position of median line, indicating that the comprehensiveness of the two indexes is strong [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the identification time of the overall basketball content meets the requirements of men's basketball Asian Championship 2020. e results are shown in Figure 6. In addition, in terms of experimental environment and experimental effect, the results of basketball program are ideal, which is basically in the position of median line, indicating that the comprehensiveness of the two indexes is strong [30].…”
Section: E Identification Time Of Basketball Schemementioning
confidence: 98%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%